"'Sink or swim': buoyancy and coping in the cognitive test anxiety – academic performance relationship". Issue 10 (25th November 2016) - Putwain, David W.; Daly, Anthony L.; Chamberlain, Suzanne; Sadreddini, Shireen
Abstract : This study explores the relationship between students' self-report levels of cognitive test anxiety (worry), academic buoyancy (withstanding and successfully responding to routine school challenges and setbacks), coping processes and their achieved grades in high-stakes national examinations at the end of compulsory schooling. The sample comprised 325 English students in their final year of secondary school preparing for high-stakes examinations. While controlling for prior attainment and gender, higher worry predicted lower examinations scores. This was partially mediated by less use of effective pre-exam coping strategies. Academic buoyancy moderated the indirect relationship such that the indirect negative relationship from worry to examination performance was stronger when academic buoyancy was lower. The paper concludes that providing in-school training in task-focus and orientation and how to withstand academic pressures may help to ameliorate the influence of performance-interfering worries, and potentially enhance performance among students inclined to worry about examinations.